Pemanfaatan Pati Sagu Pregelatinasi Taut Silang Fosfat sebagai Matriks Tablet Lepas Lambat Natrium Diklofenak - Nawatila, Roisah; Wati, Annisa Mahdia; Varasvasti, Jyestha; Aulia, Frea Widia; Avanti, Christina (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
Sustained release tablets include any drug delivery system that achieves slow release of drug over an extended period. Diclofenac sodium has a relatively short biological half-life (1-2 hours), it can be formulated into a sustained release tablet. Sago starch has the potential to be developed as a matrix for sustained release tablets. The aim of this study was to utilize sago starch which has been modified using pregelatinizing and phosphate cross linked techniques (PSTF), to be developed into a diclofenac sodium sustained release matrix. In this study, PSTF was prepared at concentration of 20% (F2); 22,5% (F3); 25% (F4); 27,5% (F5); 30% (F6); 32,5% (F7). In addition, HPMC as a synthetic hydrophilic matrix was used as reference formula (F1) at 20%. The method used in this study was wet granulation. Tablets that were produced were then tested for physical quality and drug release (at 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 hours). The results of the physical quality tablet showed that all formulas met specifications, although F1 had the lowest hardness (4,15 Kp+0,63). The results of drug release profile of F1 showed that 3,05% of drug was released during first 1 hours, while 54,07% drug was released within initial 5 hours, and the remaining 45% of the drug was released in remaining 5 hours. In addition, the drug release of F2-F7 at the 1 hours was 89,69%; 56,01%; 85,96%; 65,67%; 68,71%; 85,73%, respectively. It can be concluded that PSTF has not provided a sustained release pattern of drug.